Meckel’s diverticulum detected by computed tomographic enterography: Report of 3 cases and review of the literature - Lee, Jae Min; Jeen, Chan Dong; Kim, Seung Han; Lee, Jong Soo; Nam, Seung Joo; Choi, Hyuk Soon; Kim, Eun Sun; Keum, Bora (Turkish Journal of Gastroenterology, 2014)
Abstract Meckel’s diverticulum is a common anomaly of the small intestine and occasionally presents as obscure gastrointestinal hemorrhage. Before operation, it is difficult to diagnose by imaging, especially in adults. Conventional abdominal computed tomography and endoscopy have limitations for the diagnosis of Meckel’s diverticulum. Diagnostic methods in patients with small bowel lesions include enteroclysis, angiography, push enteroscopy, and capsule endoscopy; however, all of these techniques have low diagnostic yields to detect Meckel’s diverticulum. Recently, computed tomographic enterography has been reliable in assessing small bowel disease. We present 3 cases of Meckel’s diverticulum with bleeding in adults who were diagnosed by computed tomographic enterography. The bleeding source was not found in the total colonoscopy, and Tc-99m pertechnetate scans were negative in these patients. However, outpouching structures of the distal ileum with enhancement were detected by computed tomographic enterography. All patients underwent small bowel segmental resection. Meckel’s diverticulum was confirmed by histopathology of the resected ileum segment, and the type of heterotopic tissue was gastric mucosa.